2015
DOI: 10.1002/ejoc.201500508
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Amplification Coupling Enantioselective Autocatalysis and Asymmetric Induction for Alkylation of Azaaryl Aldehydes

Abstract: Herein, we describe a chemical system combining asymmetric amplification of Soai's autocatalyst alongside a catalytic addition of Zn(iPr) 2 to azaaryl aldehydes. Thus, Soai autocatalyst is amplified in situ from 11 to Ͼ 98 % ee and concomitantly catalyzes the alkylation of pyridine aldehydes to pro-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 41 publications
1
7
2
Order By: Relevance
“…This explains also the excellent selectivities of the 2‐(adamantylacetylene‐1‐yl)‐ and 2‐(trimethylsilylacetylene‐1‐yl)‐substituted pyrimidyl alcohols [10c, 37] . Furthermore these mixing experiments are in good agreement with the experiments by Amedjkouh using pyrimidine alcohol 1 as chiral additive in the Soai reaction of pyridyl‐3‐carbaldehydes [12d, 48] …”
Section: Resultssupporting
confidence: 83%
“…This explains also the excellent selectivities of the 2‐(adamantylacetylene‐1‐yl)‐ and 2‐(trimethylsilylacetylene‐1‐yl)‐substituted pyrimidyl alcohols [10c, 37] . Furthermore these mixing experiments are in good agreement with the experiments by Amedjkouh using pyrimidine alcohol 1 as chiral additive in the Soai reaction of pyridyl‐3‐carbaldehydes [12d, 48] …”
Section: Resultssupporting
confidence: 83%
“…al ., 2015) to show chiral erosion. 42 We have been unable to reproduce the observation reported by Amedjkouh et al Instead, we have observed amplifying autocatalysis for both substrates – diisopropylzinc alkylation of 5-(t-butylethynyl)pyridine-3-carbaldehyde also demonstrates amplifying autocatalysis (See Supplementary Figure 2 ).…”
Section: Resultscontrasting
confidence: 65%
“…However, in 2006, Wang et al developed a one-pot alkynylation-isomerizationalkynylation sequence for coupling aldehydes and alkynes without a transition-metal catalyst for the synthesis of 1-en-4-yn-3ols. [37][38][39] During our investigations, an interesting rearrangement was observed with electron-deficient alkynes under the same reaction conditions, which gave rise to heteroaromatic enone. However, the reaction was limited to substituted phenyl acetylenes.…”
Section: Introductionmentioning
confidence: 64%
“…[35,36] We have recently reported on the use of the Soai's autocatalyst in the asymmetric alkynylation of azaaryl aldehydes with various zinc acetylinides. [37][38][39] During our investigations, an interesting rearrangement was observed with electron-deficient alkynes under the same reaction conditions, which gave rise to heteroaromatic enone. Such isomerization occurred spontaneously in situ without the addition of any base or transition metal.…”
Section: Introductionmentioning
confidence: 64%